Improving Learning Processes With Online Teaching - Febri Liantoni; Rachman Arief; Nanang Fakhrur Rozi (LPPM of NAROTAMA UNIVERSITY, 2019)
Institutions of higher education do not only act as media for the educational process but must also become learning organizations. Various learning support facilities are widely available in this age of technology. One means that can be used is the Internet. The internet is a useful tool for accessing information in various formats from all over the world. The internet provides convenience in the world of education as a learning medium. Based on these conditions, online lecture training is conducted with the aim of improving the learning process during lectures. The training is carried out with Google classroom application material and the creation of learning video content. Using Google classroom can give students access to online learning. The training is carried out by direct practice using each lecturer's notebook. The results obtained during the training showed very high lecturer enthusiasm. The training makes the lecturers have the ability to better manage the lecture material, the skills of lecturers also increase by doing the practice directly. The ability of lecturers in interpersonal communication also increases with class collaboration. Through training can make changes in cognitive abilities, motor skills, values ??of affection, emotional values, and spiritual values.